2015
DOI: 10.1016/j.jmst.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterizations and Applications of Cadmium Chalcogenide Nanowires: A Review

Abstract: Cadmium chalcogenide nanowires have demonstrated superior electrical and optical properties, and have emerged as prominent building blocks for nanoscale electronic and optoelectronic devices. In addition to the effort devoted to advance techniques of fabricating high quality nanowires, much has been endeavored to elucidate their unique physical properties for better design and development of functional devices with low power consumption and high performance. Herein, this article provides a comprehensive review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 152 publications
0
5
0
Order By: Relevance
“…In the II-VI group, CdS is a direct bandgap (∼2.42 eV) semiconductor and has many potential technological applications. It can be used in light detectors, photo-conductors, green lasers, waveguides, gas sensors, biological labels, and as a window layer in solar cells [36,37]. Several attempts have been made to dope Ni 2+ ions into CdS nanostructures to improve conductivity [12,38], enhance photo-catalytic activity [39], and obtain FM [20,40].…”
Section: Introductionmentioning
confidence: 99%
“…In the II-VI group, CdS is a direct bandgap (∼2.42 eV) semiconductor and has many potential technological applications. It can be used in light detectors, photo-conductors, green lasers, waveguides, gas sensors, biological labels, and as a window layer in solar cells [36,37]. Several attempts have been made to dope Ni 2+ ions into CdS nanostructures to improve conductivity [12,38], enhance photo-catalytic activity [39], and obtain FM [20,40].…”
Section: Introductionmentioning
confidence: 99%
“…• Nanowires: Chalcogenide nanowires are one of the most promising nanostructures, with applications ranging from electronics to sensing [20]. For instance, tellurium nanowires, produced through methods like the vapor-liquid-solid (VLS) technique, are used in phase-change memory devices, offering highspeed data storage and low power consumption.…”
Section: Nanoscalementioning
confidence: 99%
“…It was shown that CdS nanowires have a direct band gap resulting in light emission/absorption in the visible range, while CdTe nanowires exhibit a high absorption coefficient and an optimal band gap for solar cell applications. 24 Furthermore, Wang et al studied the zero-dimensional structures of Cd and predicted that Cd-based clusters generate delocalized π-electron channels, which are used as photoelectrochemical-type photodetectors. 25 Moreover, Ganiga et al reported that quantum dot (QD) CdS is a fluorescence recoverer, therefore it is a promising candidate that can be used in advanced biological sensors.…”
Section: Introductionmentioning
confidence: 99%